(untitled) (GEOMATE Journal, 2024)
Environmentally friendly, high-output, high-efficiency compact pumps are in high demand in industrial fields such as chemical analysis and medical care. The efficiency of many small pumps is rather low, with peak efficiencies on the order of about 2%, even for commercially available pumps. Considering current environmental issues, improving the efficiency of motors and pumps is an important issue for preventing global warming. In this research, a small two-valve pump that can suck and discharge water by converting the energy of electromagnetic-vibration component resonance into kinetic energy was newly developed. In actual machine tests, two types of electromagnetic vibration pumps (I and II) with two-valve structures and different shapes were prototyped, and the shapes were optimized for efficiency. The type II vibration pump with an acrylic rod attached to the type I pump had excellent suction and discharge characteristics. The maximum efficiency was 12.2%, which is exceptional for a small pump. In addition, it was clarified by the actual machine test that the type II pump can stably discharge water at a high head of 2000 mm. The two types of pumps proposed in this paper were shown to be highly useful industrially in terms of performance, simplicity, cost, and operability and can be used selectively according to the application. Furthermore, since these pumps can be manufactured with a small number of parts, this paper shows their potential to contribute to environmental issues.